2010
DOI: 10.1097/tp.0b013e3181f6e267
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Macroencapsulation of Pig Islets Allows Correction of Streptozotocin-Induced Diabetes in Primates up to 6 Months Without Immunosuppression

Abstract: Pig islets encapsulated in a subcutaneous macrodevice can control diabetes up to 6 months without immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
186
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(191 citation statements)
references
References 24 publications
2
186
1
2
Order By: Relevance
“…Expression of B4GALNT2 in human cells significantly increased antibodydependent complement-mediated lysis when these cells were challenged with serum from pig-to-baboon cardiac xenotransplantation sensitized recipient serum [25] while its deletion in pig PBMCs efficiently reduced human IgG and IgM binding and decreased human anti-porcine cytotoxicity [26,27]. The fact that a strong humoral response was detected in nonhuman primates receiving alginate-encapsulated islets especially against αGal [28,29] further emphasizes the necessity to use GGTA1-KO pigs as a background for other genetic modifications. Instant blood-mediated inflammatory reaction (IBMIR) is initiated upon contact between host blood and xenografted tissue.…”
Section: Modification Of Donor Pigs To Mitigate the Immunementioning
confidence: 91%
“…Expression of B4GALNT2 in human cells significantly increased antibodydependent complement-mediated lysis when these cells were challenged with serum from pig-to-baboon cardiac xenotransplantation sensitized recipient serum [25] while its deletion in pig PBMCs efficiently reduced human IgG and IgM binding and decreased human anti-porcine cytotoxicity [26,27]. The fact that a strong humoral response was detected in nonhuman primates receiving alginate-encapsulated islets especially against αGal [28,29] further emphasizes the necessity to use GGTA1-KO pigs as a background for other genetic modifications. Instant blood-mediated inflammatory reaction (IBMIR) is initiated upon contact between host blood and xenografted tissue.…”
Section: Modification Of Donor Pigs To Mitigate the Immunementioning
confidence: 91%
“…Lymphocytes and monocytes were nevertheless detected adjacent to the transplant site, and anti-porcine IgG levels were again strongly increased, suggesting encapsulation was unable to fully immunoisolate the xenograft. Furthermore, the fi ndings reinforced the similarity of immune-mediated rejection of encapsulate islets in both the primate and mouse/rat models [ 90 ].…”
Section: Understanding Xenograft Rejection In Nonhuman Primate Recipimentioning
confidence: 74%
“…Finally, the most recent of these studies showed that both microencapsulation and macroencapsulation devices could protect adult porcine islets from humoral rejection and T-cell mediated cytotoxicity, implanted in either the kidney capsule or peritoneal compartment of primates. The macroencapsulation device also corrected hyperglycemia in the NHP models for up to 6 months without immunosuppression [ 90 ]. Lymphocytes and monocytes were nevertheless detected adjacent to the transplant site, and anti-porcine IgG levels were again strongly increased, suggesting encapsulation was unable to fully immunoisolate the xenograft.…”
Section: Understanding Xenograft Rejection In Nonhuman Primate Recipimentioning
confidence: 90%
“…WT pig (e.g., DU, GLW, Landrace, and miniature) islet xenotransplantation has successfully reversed diabetes in primate models (Hering et al, 2006;Dufrane et al, 2010;Thompson et al, 2012). However, there is a significant loss of the transplanted cells on exposure to fresh recipient blood and heterologous antigen, known as instant blood-mediated inflammatory reaction (IBMIR), as well as subsequent humoral and T-cell response that results in xenorejection of islet grafts (Nilsson, 2008;Ekser and Cooper, 2010).…”
Section: Genetically Engineered Pig: An Alternative Selection Of Islementioning
confidence: 99%
“…At present, only islet xenografts isolated from neonatal (2-3 d) and adult pigs (>6 months) display the ability to reverse diabetes in non-human primates (NHPs) or humans (Hering et al, 2006;Elliott et al, 2007;Dufrane et al, 2010;Thompson et al, 2012).…”
Section: Optimum Age Of Donor Pigmentioning
confidence: 99%